ROBOT LENGAN HUMANOID SEBAGAI ALTERNATIF PEMINDAH GELAS KIMIA - Novian Fajar Satria; Ilham Putra Prasetyo Sunardi (Jurnal Mekanova: Mekanikal, Inovasi dan Teknologi, 2020)
Robot can help humans to do their job easier and save them from dangerous work. The work is dangerous because humans sometimes do mistakes. In the laboratory, a little carelessness can cause the transmission of various catastrophic diseases such as AIDS, hepatitis B, hepatitis C, herpes, malaria, and tuberculosis. Therefore, in this paper, we propose a humanoid robot arms as an alternative to move chemical beakers. The design of the robot is divided into 3 parts namely mechanical, hardware, and software. The mechanics consist of parts of the robot’s fingers, the robot's arm, the robot's shoulder, and the robot's base that uses plastic material with 3D print. The hardware of the robot is based on a microcontroller using Arduino Nano. The finger of the robot pulled by the micro servo that is controlled by a 4.5-inch flex sensor by utilizing the resistivity of the flex sensor. Based on the results of tests that have been carried out obtained good results, with the value of the flex sensor can change every  bend not proportional to the servo angle. Based on the flex sensor feedback on the glove and robot's fingers, we know that the error in the thumb is 0.01357, on the index finger is 0.01065, on the middle finger is 0.00956, on the ring finger is 0.00893, and on the finger pinkie of 0.01193. The conclusion obtained from this study is that the humanoid robot arm can protect us from accident caused by human error in the laboratory.Keywords—Humanoid Hand Robot, Arduino, Flex Sensor